Green Screencare as a Spiritual Resistance: The Convergence of Ecofeminism and Ecotheology in Safira Natural’s Digital Narratives - Farodisatul Insaniyah; Ida Rochmawati (Journal of Indonesian Digital Islamic Studies, 2026)
The escalation of the climate crisis demands a transformation towards sustainable consumption patterns, but the gap between cognitive awareness and actual environmentally friendly practices remains a major challenge. This article examines the role of social media in bridging this gap through a case study of the Instagram account @safianatural. By combining Vandana Shiva’s ecofeminist perspective with Seyyed Hossein Nasr’s ecotheology, this study analyzes how digital narratives shape the ecological awareness of Muslim consumers. Findings show that @safianatural does not merely market beauty products, but transforms skincare practices into a framework of ecological piety. Through the convergence of discourse on women’s empowerment as guardians of nature’s sustainability and theological views on nature as theophany, consumption is reframed as a spiritual practice that restores harmony between God, humans, and the environment. Thus, social media serves as an effective theological-political arena for instilling a new consumer ethic, in which purchasing environmentally friendly products is interpreted as a manifestation of humanity’s responsibility as khalīfah on earth in the face of environmental degradation.